BENCANA ALAM DALAM PERSPEKTIF AL-QURâAN DAN BUDAYA MADURA - Muhlis, Achmad (STAIN PAMEKASAN, 2012)
Abstrac:Natural disasters occurring in this country always effect a deep grief to the people. Despite the fact that a number of rhetoric have beenÂ reconstructed to overcome the disasterÂ from new order up to reformation order. Unfortunately, this is not supported by a concrete action. The questions are that weather the disaster isÂ either an admonition or a punishment given by Allah?Â Why Allah rebukes this country so terribly. This short paper is about to disclose theÂ meaning behind the disaster from the view point of al-QurâanKeyword:bencana alam, murka Allah, tolak balaâ